Plombage: A Forgotten Surgical Treatment for Pulmonary Tuberculosis - Vakil, Abhay; Bulathsinghala, Chinthaka P.; Zanoria, Sheila J.; Surani, Salim (Current Respiratory Medicine Reviews, 2017)
Background: For several years, surgical therapies have been the mainstay for treatment of pulmonary tuberculosis. However, due to higher complication rates and the advent of potent antituberculosis (anti-TB) medications, the use of surgical therapies has declined. With the increase in the incidence of drug-resistant tuberculosis and failure to achieve satisfactory cure rates with anti-TB medications, surgical treatment might be resurging. Case Report: We recently encountered a patient who had a successful plombage therapy for the treatment of pulmonary tuberculosis. Thereby, different surgical approaches and supporting evidence for their role in the treatment of pulmonary tuberculosis in recent years has been reviewed. Conclusion: Clinicians need to be aware of this therapy, when encountering plombage on the routine x-ray chest.
Keywords: surgery